HISTORICAL-LEGAL AND ECONOMIC FEATURES OF PRE-COOPERATION FORMATION IN THE CONDITIONS OF COMMUNITY SOCIETY - Nevleva, Inna; Nevlev1, Vladimir; Nevlev, Vladislav; Solovyeva, Larisa; Solovyeva, Vladislava; Nevleva, Anastasia (Revista Inclusiones, 2020)
In the theory of the international cooperative movement, the time of the legal birth of cooperation is considered to be the beginning of the 18th – the end of the 19th centuries. This historical period is characterized by the stratification of the social composition of society into the bourgeoisie and hired workers, which served as the economic and legal reason for the creation of cooperatives. However, social classes, divided into the oppressors and the oppressed, have always existed, except for a classless primitive society. The emergence of elements of primitive cooperation, or precooperation, has been observed throughout world history.